LEARNING ACHIEVEMENT IS REVIEWED FROM TEACHER COMPETENCE, PARENTAL ATTENTION, MOTIVATION AND LEARNING FACILITIES - Siti Nurhayati; Bambang Mursito; Sarsono Sarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study is to examine and quantify the effect of teacher competency, parental attention, motivation, and learning facilities on the academic achievement of students at SMK Negeri 1 Sragen. This research method is quantitative in nature. The population of this study was comprised of all pupils in class X of SMK N 1 Sragen, a total of 468 students, with a sample size of 117 respondents. Questionnaires were used to collect data. Statistical analysis employs a multiple linear regression test, which is done using the SPSS 24 software. On the basis of the findings of hypothesis testing and debates, it may be inferred that teacher competence and learning motivation are related. Positive and significant influence on the learning accomplishment of students at SMK Negeri 1 Sragen, but parental attention is both influential and inconsequential, while learning facilities have no effect and are negligible on the learning achievement of students at SMK Negeri 1 Sragen. Keywords: competence, motivation, achievement, parental attention, learning facilities